Combined use of Mössbauer spectroscopy, XPS, HRTEM, dielectric and anelastic spectroscopy for estimating incipient phase separation in lead titanate-based multiferroics. Issue 21 (17th May 2018) - Craciun, Floriana; Cordero, Francesco; Vasile, Bogdan S.; Fruth, Victor; Zaharescu, Maria; Atkinson, Irina; Trusca, Roxana; Diamandescu, Lucian; Tanase, Liviu C.; Galizia, Pietro; Cernea, Marin; Galassi, Carmen
Abstract : Incipient phase separation is revealed in a multiferroic by combined spectroscopic techniques. Abstract : The formation of separate phases in crystalline materials is promoted by doping with elements with different valences and ionic radii. Control of the formation of separate phases in multiferroics is extremely important for their magnetic, ferroelectric and elastic properties, which are relevant for multifunctional applications. The ordering of dopants and incipient phase separation were studied in lead titanate-based multiferroics with the formula (Pb0.88 Nd0.08 )(Ti0.98− x Fe x Mn0.02 )O3 ( x = 0.00, 0.03, 0.04, 0.05) by means of a combination of Mössbauer spectroscopy, XPS, HRTEM, dielectric and anelastic spectroscopy. We found that Fe ions are substituted as Fe 3+ at Ti sites and preferentially exhibit pentahedral coordination, whereas Ti ions have coexisting valences of Ti 4+ /Ti 3+ . Fe 3+ ions are preferentially ordered in clusters, and there exists a transition temperature T C1, below which phase separation occurs between a tetragonal phase T1 free of magnetic clusters and a cubic phase, and a lower transition temperature T C2, below which the cubic phase rich in magnetic clusters is transformed into a tetragonal phase T2. The phase separation persists at the nanoscale level down to room temperature and is visible in HRTEM images as a mixing of nanodomains with different tetragonality ratios. This phase separation was observed over the whole studied concentration range of x Fe values. It occurs progressively with the value of x Fe, and the transition temperature T C2 decreases with the concentration from about 620 K ( x Fe = 0.03) to about 600 K ( x Fe = 0.05), while T C1 remains nearly constant.